A genome‐wide association study identifying SVEP1 variant as a predictor of response to tolvaptan for cirrhotic ascites. (8th August 2021) - Kawaratani, Hideto; Sawai, Hiromi; Onishi, Masaya; Kogiso, Tomomi; Shimada, Noritomo; Uojima, Haruki; Nakajima, Tomoaki; Matsumoto, Naoki; Ikejima, Kenichi; Ishikawa, Toru; Terai, Shuji; Motoyama, Hiroyuki; et al.
Abstract: Background & Aims: Tolvaptan, vasopressin V2‐receptor antagonist, has been used for patients with difficult‐to‐treat ascites in Japan. In this study, we conducted a genome‐wide association study (GWAS) in the Japanese population to identify genetic variants associated with tolvaptan's efficacy for patients with hepatic ascites. Methods: From 2014 through 2018, genomic DNA samples were obtained from 550 patients who were treated with tolvaptan. Of those, 80 cases (non‐responder; increase of body weight [BW]) and 333 controls (responder; >1.5 kg decrease of BW) were included in the GWAS and replication study. Results: Genome‐wide association study showed 5 candidate SNPs around the miR818, KIAA1109, and SVEP1 genes. After validation and performing a replication study, an SNP (rs2991364) located in the SVEP1 gene was found to have a significant genome‐wide association (OR = 3.55, P  = 2.01 × 10 ‐8 ). Multivariate analyses showed that serum sodium (Na), blood urea nitrogen (BUN) and SVEP1 SNP were significantly associated with the response (OR = 0.92, P  = .003; OR = 1.02, P  = .02 and OR = 3.98, P  = .000008, respectively). Based on a prediction model of logistic regression analysis in a population with the rs2991364 risk allele, the failure probability (=exp (score: 22.234 + BUN*0.077 + Na*‐0.179) (1 + exp (score)) was determined for the detection of non‐responders. Assuming a cutoff of failure probability at 38.6%, sensitivity was 84.4%, specificity was 70% and AUC was 0.774. Conclusion: SVEP1 rs2991364 was identified as the specific SNP for the tolvaptan response. The prediction score (>38.6%) can identify tolvaptan non‐responders and help to avoid a lengthy period of futile treatment.